Computed Tomographic Assessment of Renal Volume and Its Associative Factors Among Adults - Sah, Ramswarth; Bhattarai, Mamata; Pradhan, Bijay Lal; Shrestha, Shanta Lall; Lohani, Benu; Bhatta, Ramesh (Journal of Nepal Health Research Council, 2021)
Background: Knowledge of normal renal volume is a vital parameter for clinical assessment of renal diseases because renal size is altered by various medical conditions. Variations in renal dimension in different populations and it’s relation to individual’s body parameters are evident. Different studies have recommended the need for measurement of renal dimension for specific population. This study assesses normal range of renal volume in the study population and measures their correlation with individual’s body parameters.Methods: This descriptive study was done in 261 adults. After renal length measurement on reformatted coronal images, renal width and renal thickness on axil images, renal volume was calculated by ellipsoidal formula. Descriptive statistics and parametric tests were used to evaluate the association between renal volume and different parameters.Results: This study showed a significant difference in mean renal volume between male (right and left mean renal volume 120.52 ± 26.84 cm3 and 121.00 ± 27.23 cm3 respectively) and female (right and left mean renal volume 110.11 ± 21.79 cm3 and 111.15 ± 22.34 cm3 respectively) on each side. Similarly, a significant positive correlation was found between renal volume and body height, body weight and BMI of participant for both kidneys however a significant negative correlation was observed between renal volume and age 40 years and above for both kidneys.  Conclusions: This study provides morphometric data regarding normal kidneys and concludes that male renal volume is more than female and renal volume is correlated to individual’s body parameters.Keywords: Morphometric; nomogram; renal volume